Sustainable Campus: An Integrated Student Knowledge, Waste (WS), Energy and Climate Change (EC) for Recognition in “UI-Green Metric World College Ranking” - Bakar, Mohd Norazwan A.; Salleh, Hamdan M.; Rahim, Nasrudin Md; Ne'Matullah, Khairul Firdaus; Idris, Zahirrudin (Selangor Humaniora Review, 2021)
Institutions of Higher Learning in Malaysia, which serves as an educational and research institution, need to emphasize sustainability to ensure a continuous effort in maintaining it. The management of UNISEL is deemed desirable to provide more sustainable campus-based programs more regularly and continuously so that the practice can be used as a culture of sustainability in their daily lives. However, a low acceptance from the community, especially the campus sustainability efforts, makes it difficult for it to continue as there are no strong support and a high awareness of the importance of environmental care. The objective of this study was to identify the level of knowledge and awareness of students on sustainable campuses to support efforts to improve UNISEL’s position in the “UI Green Metric World University Ranking”. Distribution of questionnaires carried out and involved a total of 2154 respondents. The study found that the level of knowledge, awareness, and practice of UNISEL’s members is low and should be improved.